PENGARUH LIKUIDITAS, PRICÎ• Î•ARNING RATÎ™O (PÎ•R) DAN DÎ™VÎ™DÎ•ND PÎ•R SHARÎ• (DPS) PADA HÎ‘RGÎ‘ SÎ‘HÎ‘M - Putra, Wijaya; Stefahni, .; Sitohang, Karina F.; Govanni, Jessyln; Anneliese, .; Ricke, .; Mesrawati, .; Hayati, Sukma (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The research had purpose to analyzed the effect of liquidity, PÎ•R and DPS on stock price. Independent variables that used in this study were liquidity, price earning ratio and dividend per share. Dependent variable that used was stock price. The population are all the property and real estate companies listed on the Indonesia Stock Exchange in Indonesia 2012-2017. Methods of analysis used was multiple linear regression. The research used purposive random sampling method, that is the samples of 14 companies. The results of partial test shows that liquidity does not affect the stock price,then the effect of PÎ•R and DPS on the stock price were significant. Simultaneously the effect of liquidity, PÎ•R and DPS were significant to the company's stock price in the property and real estate companies listed in Indonesia Stock Exchange in 2012-2017 periods.Keywords: Liquidity, Price Earning Ratio, Dividend Per Share, Stock Prices